2016
DOI: 10.1088/0029-5515/56/6/064002
|View full text |Cite
|
Sign up to set email alerts
|

Collisionless pitch-angle scattering of runaway electrons

Abstract: It is discovered that the tokamak field geometry generates a pitch-angle scattering effect for runaway electrons. This neoclassical pitch-angle scattering is much stronger than the collisional scattering and invalidates the gyro-center model for runaway electrons. As a result, the energy limit of runaway electrons is found to be larger than the prediction of the gyro-center model and to depend heavily on the background magnetic field.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 51 publications
(98 reference statements)
5
46
2
Order By: Relevance
“…For example, at t = 3. agrees with the numerical results in Ref. [26] and offers a direct description of the origin of collisionless pitch-angle scattering.…”
Section: Runaway Dynamics In T C -Timescalesupporting
confidence: 90%
See 4 more Smart Citations
“…For example, at t = 3. agrees with the numerical results in Ref. [26] and offers a direct description of the origin of collisionless pitch-angle scattering.…”
Section: Runaway Dynamics In T C -Timescalesupporting
confidence: 90%
“…Because it has been proved that the gyro-center model breaks down for the dynamics of energetic runaway electrons [26], the motion of runaways in Besides the outward neoclassical drift orbit similar to the results from the gyrocenter code [25,30], it can also be observed that there exist ripple structures superimposed on each circle orbit. These fine ripple structures, which cannot be recovered by gyro-center models, correspond to the runaway motion in T c -timescale and become more obvious as time going.…”
Section: Runaway Dynamics In T C -Timescalementioning
confidence: 66%
See 3 more Smart Citations